Captives : How Stolen People Changed the World - Cameron, Catherine M. (Book collections on Project MUSE., 2016)
"Using a comparative approach, a detailed study of captive-taking in small-scale societies and exploration of the profound impacts that captives had on the societies they joined. Opens new avenues of research about captives as significant sources of culture change"--